Structural brain correlates of response inhibition in obsessive-compulsive disorder - Chia, Kai Xin (2015)
Obsessive-compulsive disorder (OCD) can be a chronically debilitating illness and prevalence of OCD is marginally higher in Singapore. The exact neural mechanisms contributing to this disorder are not fully understood. In more recent years, functional and structural abnormalities in the orbitofrontal-striatal-thalamic circuit and dorsolateral-prefrontal-striatal circuit have been proposed to underlie OCD pathophysiology. However, present literature on structural abnormalities remains inconsistent and limited studies have addressed the gap between structural abnormalities and cognitive deficits in OCD. Hence, the current study consolidated past structural findings and investigated structural abnormalities in patients with OCD using voxel-based morphometry. Structural correlates of response inhibition, a neurocognitive endophenotype of OCD, were also examined. Contrary to past literature, our sample of patients with OCD exhibited superior response inhibition performance compared to healthy controls. Striatum volumes were not correlated with response inhibition performance. Increased grey matter volumes were found in the inferior frontal gyrus, putamen and hippocampal regions. White matter volume abnormalities included the cingulate gyrus, inferior longitudinal fasciculus and thalamus. The present findings of structural abnormalities in the putamen, cingulate and thalamus are consistent with the proposed neural circuits. Additionally, differences found in the occipito-temporal regions contributed to the understanding of OCD pathophysiology. Keywords: obsessive-compulsive disorder, morphometry, response inhibition